A Triple Obstetric Challenge of Thoracopagus-Type Conjoined Twins, Eclampsia, and Obstructed Labor: A Case Report from Sub-Saharan Africa. (5th December 2017) - Leigh, Mariatu Binta; John-Cole, Valerie; Kamara, Mike; Koroma, Alimamy Philip; Koroma, Michael Momoh; Emuveyan, Edward Ejiro; Bramlage, Peter; Buschmann, Ivo
Abstract : Conjoined twins are very rarely seen. We present a case of thoracopagus that was undiagnosed prior to delivery and combined with eclampsia and obstructed labor in a low-resource setting in sub-Saharan Africa. A 27-year-old pregnant woman was presented to the maternity emergency unit of Princess Christian Maternity Hospital (PCMH) in Freetown at term in labor. Upon admission, the patient was awake and orientated and presented a blood pressure of 180/120 mmHg and a protein value of 3+ on urine dipstick test. Clinical examination—ultrasound was not available—led to the admission diagnosis: obstructed labor with intrauterine fetal death and preeclampsia. Application of Hydralazine 5 mg (i.v.) under close blood pressure monitoring was performed. Under spontaneous progression of labor, one head of the yet unknown conjoined twin was born. The patient developed eclamptic fits. Ceasing of seizures was achieved after implementing the loading dose of the MgSO4 protocol. A vaginal examination led to the unexpected diagnosis of conjoined twins. An emergency cesarean section under general anesthesia via a longitudinal midline incision was performed immediately. The born head was repositioned vaginally. The stillborn conjoined twins presented a female thoracopagus type that seemed to involve the heart. After 8 weeks, the woman was clinically fully recovered.